Cutaneous Manifestation of Metastatic Infantile Choriocarcinoma - Timothy Brooks; Laura Nolting (Hindawi Limited, 2014)
Infantile choriocarcinoma is a highly malignant rare germ cell tumor that arises from the placenta. Simultaneous intraplacental choriocarcinoma involving both mother and infant is extremely rare. Cutaneous metastasis in infantile choriocarcinoma is even rarer with only a few case reports available. Here we describe a case of a female neonate who presented to the ED with a rapidly growing and bleeding vascular lesion to her right cheek. She was eventually diagnosed by biopsy with metastatic choriocarcinoma. In addition to the cutaneous tumor, she also had metastatic disease in her lungs. Her mother was subsequently found to have choriocarcinoma with metastatic disease to the lungs as well.